Services – SERVICES 2019 : 15th World Congress, held as part of the Services Conference Federation, SCF 2019, San Diego, CA, USA, June 25–30, 2019 : Proceedings /: 15th World Congress, held as part of the Services Conference Federation, SCF 2019, San Diego, CA, USA, June 25–30, 2019 : Proceedings. (2019) - Unknown
No abstract available